Vegetation Dynamics in the “Three Water Lines” Region of Northwest China: The Role of Climate Change and Human Activities - Xifeng Zhang; Zhongjun Li; Qiang Wang; Libang Ma (Ecosystem Health and Sustainability)
The northwest region of China is a vital ecological security barrier, with a fragile and highly sensitive environment. Understanding the dynamics of fractional vegetation coverage (FVC) and the driving factors influenced by climate change and human activities is crucial. This study extracts FVC from the normalized difference vegetation index and analyzes its spatiotemporal dynamics using the Sen + Mann–Kendall test, coefficient of variation, and Hurst index. The study also evaluates the impact of climate change and human activities on FVC using geographical detectors, correlation analysis, and multiple regression residual analysis. Results show that from 1982 to 2022, FVC in the northwest region exhibited a fluctuating upward trend (0.028%·year−1). FVC values were higher in the eastern and southern regions and lower in the western and northern regions. Areas with marked FVC fluctuations were mainly concentrated in the eastern Hu-Yang and northern Qi-North, with areas (44.15%) expected to show an anti-persistent trend. Evapotranspiration, precipitation, land use, and soil moisture were the primary factors driving FVC changes (q>0.6), and FVC showed a significant positive correlation with precipitation, temperature, evapotranspiration, and soil moisture while being negatively correlated with solar radiation and vapor pressure deficit. FVC changes in the northwest region (83.44%) were jointly driven by climate change and human activities, with climate change (54.20%) having a greater impact. This research lays a scientific foundation for a deeper understanding of FVC dynamics due to the combined effects of climate change and human activities, opening new pathways for ecological conservation and sustainable development in the region.